A new creep-fatigue crack growth model and a correlation of the creep-fatigue crack growth rate with unified constraint parameter. (January 2023) - Lu, Rong-Sheng; Tan, Jian-Ping; Yang, Jie; Wang, Ji; Shlyannikov, Valery; Wang, Run-Zi; Zhang, Xian-Cheng; Tu, Shan-Tung
Graphical abstract: Highlights: A new creep-fatigue crack growth (CFCG) model was proposed and verified. The unified constraint parameter, Ap, was extended to creep–fatigue loading. The CFCG rate has a linearly correlation with the unified constraint parameter, Ap . Abstract: Creep-fatigue and constraint are important factors affecting the fracture behavior and service life of components in high-temperature service. Some researchers have attempted to describe creep-fatigue crack growth (CFCG) behavior using constraint parameters. However, there is still no consensus regarding the effect of the constraint on the CFCG rate, and a correlation between the constraint and the CFCG rate must be established. Thus, in this study, a new CFCG model was developed and verified by finite element simulations and experiments. Then, the CFCG behavior for single edge-notched tensile (SENT), centre-cracked tension (CCT), and compact tension (CT) specimens under different constraint conditions was studied using the new model to reveal the effect of constraint on the CFCG rate. The relationship between the dwell time and the CFCG rate was also studied. Moreover, a linear correlation between the CFCG rate and the constraint was established for the first time using the unified constraint parameter Ap, and it is shown that the CFCG rate has a strong correlation with the area surrounded by the equivalent plastic strain ( εp ) contour at the crack tip. This indicates that the constraint effect on the creep-fatigue could be further revealed by Ap . Furthermore, Ap was extended from monotonic loading to creep-fatigue loading, and a method is provided for using CFCG test data to evaluate high-temperature components with defects.